SMC5/6 acts jointly with Fanconi anemia factors to support DNA repair and genome stability. (23rd December 2019) - Rossi, Francesco; Helbling‐Leclerc, Anne; Kawasumi, Ryotaro; Jegadesan, Nanda Kumar; Xu, Xinlin; Devulder, Pierre; Abe, Takuya; Takata, Minoru; Xu, Dongyi; Rosselli, Filippo; Branzei, Dana
Abstract: SMC5/6 function in genome integrity remains elusive. Here, we show that SMC5 dysfunction in avian DT40 B cells causes mitotic delay and hypersensitivity toward DNA intra‐ and inter‐strand crosslinkers (ICLs), with smc5 mutants being epistatic to FANCC and FANCM mutations affecting the Fanconi anemia (FA) pathway. Mutations in the checkpoint clamp loader RAD17 and the DNA helicase DDX11, acting in an FA‐like pathway, do not aggravate the damage sensitivity caused by SMC5 dysfunction in DT40 cells. SMC5/6 knockdown in HeLa cells causes MMC sensitivity, increases nuclear bridges, micronuclei, and mitotic catastrophes in a manner similar and non‐additive to FANCD2 knockdown. In both DT40 and HeLa systems, SMC5/6 deficiency does not affect FANCD2 ubiquitylation and, unlike FANCD2 depletion, RAD51 focus formation. SMC5/6 components further physically interact with FANCD2‐I in human cells. Altogether, our data suggest that SMC5/6 functions jointly with the FA pathway to support genome integrity and DNA repair and may be implicated in FA or FA‐related human disorders. Synopsis: The structural maintenance complex SMC5/6 interacts with and functions jointly with key components of the Fanconi anemia pathway to facilitate DNA repair and preserve genome stability. SMC5/6 dysfunction causes mitotic delays and DNA damage sensitivity. SMC5/6 functions jointly with FA components and FA‐like pathways in DNA repair. SMC5/6 acts jointly with FANCD2 to prevent micronuclei and mitotic aberrations. SMC5/6 interacts with FANCD2‐I without affecting FANCD2‐I ubiquitylation. Abstract : The structural maintenance complex SMC5/6 interacts with and functions jointly with key components of the Fanconi anemia pathway to facilitate DNA repair and preserve genome stability.